Pemanfaatan E-Commerce dalam Meningkatkan Pendapatan UMKM di Medan Perjuangan - Ardiansyah Ardiansyah; Novien Rialdy (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
The rapid development of digital technology has accelerated the transformation of business models, particularly within the Micro, Small, and Medium Enterprises (MSMEs) sector. One significant form of this transformation is the adoption of e-commerce as a platform for digital marketing and business transactions. This study aims to analyze the role of e-commerce in increasing the income of MSMEs in Medan Perjuangan District. The research employs a qualitative approach using secondary data obtained from government reports, scientific journals, and relevant previous studies. Data were analyzed through content analysis to identify patterns and key findings related to e-commerce utilization among MSMEs. The results show that the use of e-commerce has a positive impact on MSME income by expanding market reach beyond local boundaries, reducing marketing and operational costs, and improving consumer access and transaction convenience. However, the study also identifies major challenges, particularly limited digital literacy, inadequate technological infrastructure, and low readiness among MSME actors, which need to be addressed to maximize the benefits of e-commerce adoption.